PENERAPAN MODEL LATIHAN PENELITIAN DI SEKOLAH DASAR: KELEBIHAN, KEKURANGAN, DAN DAMPAKNYA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Miranti (Jurnal Komunikasi, 2026)
This study aims to describe the implementation of the research training model in elementary school and to examine its strengths, weaknesses, and impact on students’ critical thinking skills. The research training model is a learning approach that actively involves students in identifying problems, asking questions, gathering simple data, and drawing conclusions based on their own findings. Through this model, students are not only receiving information from the teacher but are also encouraged to think independently and discover answers by themselves. this research used a descriptive qualitative approach with observation, interviews, and documentation as data collection techniques. The results show that the implementation of the research training model improves students’ ability to analyze information, express logical opinions, and solve problems in a more structured way. Students become more active, confident in asking questions, and able to provide reasons for their answers. the strengths of this model include fostering curiosity, learning independence, and higher-order thinking skills. However, several challenges were found, such as limited instructional time and the need for teacher readiness in guiding simple research activities. Overall, the research training model has a positive impact on developing elementary students’ critical thinking skills when implemented carefully and adapted to students’ characteristics.